(untitled) (Ameghiniana, 2013)
Canid remains from Site 2 of the Archaeological Locality Zanjón Seco, Buenos Aires Province, are described and the prehispanic occurrences of Canis (Canis) familiaris Linne in the Pampean and Patagonian areas are reviewed. Evidence indicates that Canis (Dusicyon) avus (Burmeister) inhabited the Buenos Aires province until relatively recent times (Holocene) and that Canis (Canis) familiaris lived in the Pampean and Patagonian areas before the Hispanic Conquest. The problems of the systematic determination of the canid remains from Pampean and Patagonian Holocene or Recent sites are reviewed in this context. The presence and/or maintenance of the domestication process by prehispanic aborigines, and the dog’s influence on that group’s economy are considered fron the archaeological viewpoint.